2005
DOI: 10.1246/cl.2005.464
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Endohedral Metallofullerenes Using a Mixed Solvent of Triethylamine and Acetone

Abstract: We have developed a single-step method for selectively extracting endohedral metallofullerenes. In this new method, a mixed solvent of triethylamine and acetone is used to extract endohedral metallofullerenes from raw soot. The efficiency of extraction was investigated by extracting Ce-containing metallofullerenes, Ce@C82 and Ce2@C80, from raw soot obtained by an arc discharge technique. The resultant extract contained little or no empty fullerenes such as C60 or C70, that is, the Ce-metallofullerenes were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…We obtained the anion Y 2 @C 80 − through chemical reduction of the arc discharge produced soot by using trimethylamine as the reduction agent. 41 The reduced product contains anions Y 2 @C 80 − and Y@C 82 − (Figure 4d). The diamagnetic anion Y@C 82 − does not have a major influence on the ESR measurements on Y 2 @C 80 − .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We obtained the anion Y 2 @C 80 − through chemical reduction of the arc discharge produced soot by using trimethylamine as the reduction agent. 41 The reduced product contains anions Y 2 @C 80 − and Y@C 82 − (Figure 4d). The diamagnetic anion Y@C 82 − does not have a major influence on the ESR measurements on Y 2 @C 80 − .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Then, Y 2 @C 80 and Y@C 82 were selectively reduced and extracted from the raw soot. Trimethylamine (TEA) is a substantially strong electron donor and is able to reduce metallofullerenes to their anions or form donor–acceptor complex with metallofullerenes . In addition, the solvent polarity has significant influence on the reduction potential of metallofullerenes .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work provides a simple method for selective extraction of M 2 @C 80 metallofullerene. Kodama and coworkers reported that Ce-metallofullerenes (Ce@C 82 , Ce 2 @C 78 , Ce 2 @C 80 ) can be extracted selectively using a mixed solvent of triethylamine and acetone [ 61 ]. They proposed that the reduction of Ce-metallofullerenes by triethylamine or the formation of metallofullerene-triethylamine donor-accepter complexes is responsible for the selective extraction of metallofullerenes.…”
Section: Separation/purification Of Metallofullerenes Through Chemmentioning
confidence: 99%
“…Non-HPLC approaches for endohedral separations take advantage of differences between metallofullerenes and empty-cage fullerenes, which lack an electron transfer from the cluster to the cage surface due to the absence of an encapsulated metal(s). Features of emptycages and metallofullerenes that can be manipulated include differences in their physical properties, 5,6 chemical reactivity, [7][8][9][10][11][12][13][14][15][16] and electrochemical/redox [17][18][19][20][21][22][23] behaviour.…”
Section: Introductionmentioning
confidence: 99%